Characteristics of the nucleotide composition and de novo structure of 28S rRNA gene of intestinal flukes (Echinostomatidae) and genetic distance among species (suborder Echinostomata) - Thi Khanh Linh, Pham; Thi khue, Nguyen; Thi Thanh Huong, Doan; Hoa, Le Thanh (Vietnam Journal of Biotechnology, 2022)
The family Echinostomatidae includes four genera, Echinostoma, Hypoderaeum, Echinoparyphium, and Artyfechinostomum, which are of public epidemiological and pathogenic importance. The morphological similarity of species requires differentiating methods, and the use of molecular genetic markers is mainly encountered. The 28S rRNA gene sequence in the family Echinostomatidae is an important marker for the analysis of the interspecies and phylogenetic relationships. However, information about the structure and composition of the complete 28S rRNA gene in Echinostomatidae is limited. In this study, the complete 28S rRNA sequences (3,881–3,883 bp) of four species, including Echinostoma revolutum (designated Erev-MSD15-TH), E. malayanum (Emal-EMI3-TH), E. miyagawai (Emiy-RED11-TH), and Hypoderaeum conoideum (Hcon-RED42-TH) were obtained and analyzed for their genetic characteristics. All had complex secondary structures, containing numerous branches, “hairpins”, and “loops” that provide stability of the rRNA gene. The de novo structural pattern and the "skew" value in the nucleotide use of E. revolutum, E. malayanum, E. miyagawai, and H. conoideum were analyzed. The nucleotide usage of A, T, G, C and A+T and G+C of 28S rRNA in all species of the family Echinostomatidae was similar, in which A and T usage were almost equal, and G and C were slightly different in the range of 7–8%, so the skewness for AT was very low negative value (–0.029 to –0.045), and for GC was not very high (0.163 to 0.172). The genetic distance estimated among strains within a species (intra-specific level) was very low in both the Echinostomatidae (0.05%) and the Fasciolidae families (0–0.03%), and that among different species (inter-specific level) was higher. However, among species in different families (inter-familial level) the genetic distance was highest, at 3.80–4.86%, as seen between Echinostoma and Fasciola species. The 28S rRNA gene dataset obtained from four species of the intestinal flukes (family Echinostomatidae) in this study contribute to the understandings of genetic markers in the suborder Echinostomata for use in diagnostic, phylogenetic, taxonomic, epidemiological, and population genetics studies.